2007
DOI: 10.1007/s10695-006-9123-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weaning age and diets on ontogeny of digestive activities and structures of pikeperch (Sander lucioperca) larvae

Abstract: Growth and ontogeny of digestive function were studied in pikeperch (Sander lucioperca) larvae weaned on artificial food at different ages. Three weaning treatments initiated respectively on day 9 (W9), day 15 (W15) or day 21 (W21) post-hatching (p.h.) were compared with a control group, fed Artemia nauplii from first feeding until the end of the rearing trial on day 36 p.h. The digestive enzyme activities and the ontogeny of digestive structures were investigated using enzymatic assays and histological method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 36 publications
3
62
1
5
Order By: Relevance
“…Furthermore, it should be reminded that size differences that may emerge during the early life stages could vanish a few months later (Ottesen et al 2009). Under culture conditions, cannibalism is the main factor that governs fish survival, especially in larvae and juveniles of fast growing predatory species like the European sea bass (Katavić et al 1989; vundu catfish, Heterobranchus longifilis Valenciennes, 1840 (see Baras 1999); Eurasian perch, Perca fluviatilis Linnaeus, 1758 (see , Babiak et al 2004, Mandiki et al 2007); pikeperch, Sander lucioperca (Linnaeus, 1758) (see Hamza et al 2007, Szkudlarek and Zakęś 2007, Szczepkowski et al 2011; barramundi, Lates calcarifer (Bloch, 1790) (see Arockiaraj and Appelbaum 2011); and European catfish (Kozłowski andPoczyczyński 1999, Pruszyński andPistelok 1999). The results of presently reported study confirmed that cannibalism was the main contributor to the mortality of European catfish larvae and that losses to type II cannibalism outnumbered those to type I cannibalism, as documented in the vast majority of fishes under culture conditions (Braband 1995, Baras 1999, Baras et al 2000, Babiak et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be reminded that size differences that may emerge during the early life stages could vanish a few months later (Ottesen et al 2009). Under culture conditions, cannibalism is the main factor that governs fish survival, especially in larvae and juveniles of fast growing predatory species like the European sea bass (Katavić et al 1989; vundu catfish, Heterobranchus longifilis Valenciennes, 1840 (see Baras 1999); Eurasian perch, Perca fluviatilis Linnaeus, 1758 (see , Babiak et al 2004, Mandiki et al 2007); pikeperch, Sander lucioperca (Linnaeus, 1758) (see Hamza et al 2007, Szkudlarek and Zakęś 2007, Szczepkowski et al 2011; barramundi, Lates calcarifer (Bloch, 1790) (see Arockiaraj and Appelbaum 2011); and European catfish (Kozłowski andPoczyczyński 1999, Pruszyński andPistelok 1999). The results of presently reported study confirmed that cannibalism was the main contributor to the mortality of European catfish larvae and that losses to type II cannibalism outnumbered those to type I cannibalism, as documented in the vast majority of fishes under culture conditions (Braband 1995, Baras 1999, Baras et al 2000, Babiak et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During 5-8 dph, the stomach is not functional enough for artificial diets, and the digestive enzyme activities are in rapid increase (Liu, 2011). At this stage, an improper abrupt-weaning time and microdiet diets might delay the stomach development or impair epithelial cell as observed by Hamza et al (2007). Formulated feed was reported to delay or even prevent the maturation process of fish larvae ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence time and the development of key enzymes also decide weaning success (Gawlicka et al, 2000;Moyano and Sarasquete, 1993). Improper weaning age or weaning diet could damage the digestive tract and lead to chronic stress with progressive starvation (Pickering, 1998), and delay or impair the development, health and physiological function of fish larvae Fevolden and Røed, 1993;Fevolden et al, 1999;Hamza et al, 2007;Iwama et al, 2005;Wendelaar Bonga, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Conocer los cambios que ocurren en el tracto digestivo durante el desarrollo ayuda a comprender la fisiología de la nutrición en larvas y a elegir el momento óptimo para iniciar la alimentación con raciones balanceadas, evitando altas mortalidades que ocurren cuando se suministran alimentos artificiales a ejemplares que no pueden asimilarlos (Person-Le Ruyet et al, 1993;Gisbert et al, 2004;Micale et al, 2006;Hamza et al, 2007).…”
Section: Introductionunclassified
“…En este sentido, los estudios histomorfológicos durante la ontogenia del sistema digestivo son una herramienta fundamental para evaluar la potencial utilidad de diferentes dietas para larvas, así como para dilucidar relaciones funcionales entre los diferentes órganos envueltos en los procesos digestivos (Hamza et al, 2007;Önal et al, 2008;Gisbert et al, 2009;Treviño et al, 2011).…”
Section: Introductionunclassified